2019
DOI: 10.2987/19-6848.1
|View full text |Cite
|
Sign up to set email alerts
|

Gravid Culex pipiens Exhibit A Reduced Susceptibility to Ultra–Low Volume Adult Control Treatments Under Field Conditions

Abstract: In July and August of 2018, a field trial was conducted to examine the effectiveness of the North Shore Mosquito Abatement District's operational ultra–low volume (ULV) adulticide program. Two study sites were selected in Skokie, IL, and treated by truck-based ULV with d-phenothrin and prallethrin synergized with piperonyl butoxide over the course of a month. Natural mosquito populations were sampled via Biogents (BG)-counter baited with CO2 or Alfalfa infusion. The results from this study demonstrate that hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…A comparative field evaluation of the BG-Counter is not readily available in the published literature, but a limited number of reports suggest that the BG-Counter is an effective tool in a number of organized mosquito control districts in Florida, Louisiana, Illinois, and California (Biogents 2019, Clifton et al 2019, Lucas et al 2019. These states generally have a robust mosquito control infrastructure, highly abundant nuisance mosquito populations, and endemic mosquito-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative field evaluation of the BG-Counter is not readily available in the published literature, but a limited number of reports suggest that the BG-Counter is an effective tool in a number of organized mosquito control districts in Florida, Louisiana, Illinois, and California (Biogents 2019, Clifton et al 2019, Lucas et al 2019. These states generally have a robust mosquito control infrastructure, highly abundant nuisance mosquito populations, and endemic mosquito-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…An average 65.3% reduction in Cx. pipiens/restuans populations was observed within 24 hours of truck-mounted applications of a pyrethroid [52]. In contrast, no signi cant changes in Cx.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Elnaiem et al (2008) showed 75% reduction of Cx. pipiens in Sacramento decreasing the risk of WNV infection, while Clifton et al (2019) showed that pyrethroid ULV treatments decreased host seeking females 24 h after treatment by 65.3% but not gravid females in Chicago (USA), possibly not affecting infection rate of the population. In case of RVFV introduction in Europe, vector control, such as adulticide treatments, would be in place if transmission in human cases is detected, similar to WNV scenario.…”
Section: Vector Controlmentioning
confidence: 97%
“…pipiens in Sacramento decreasing the risk of WNV infection, while Clifton et al. (2019) showed that pyrethroid ULV treatments decreased host seeking females 24 h after treatment by 65.3% but not gravid females in Chicago (USA), possibly not affecting infection rate of the population.…”
Section: Assessmentmentioning
confidence: 99%